Design Error Costs in Construction Projects - Lopez, Robert; Love, Peter (ASCE Publications- American Society of Engineers, 2012)
Design errors can adversely influence project performance and can contribute to failures, accidents, and loss of life. Although there has been a considerable amount of research that has examined design error causation, little is known about design error costs. With increasing emphasis placed on the use of nontraditional forms of procurement methods as a result of various government reports and the advent of Building Information Modelling there is a general perception that design error costs will be significantly less than those projects procured by traditional means. By using a questionnaire survey, estimates for design error costs were obtained from 139 projects. The mean direct and indirect costs for design errors were revealed to be 6.85 and 7.36% of contract value, respectively. Design error costs were found not to significantly vary with procurement method and project type used. Although the research provides invaluable insights into practitioners’ perceptions of design errors costs, their actual costs remain relatively unexplored.